Phenolic Compounds From Brewer's Spent Grains: Toward Green Recovery Methods and Applications in the Cosmetic Industry - Macias-Garbett, Rodrigo; Serna-Hernández, Sergio Othón; Sosa-Hernández, Juan Eduardo; Parra-Saldívar, Roberto (Frontiers in Sustainable Food Systems, 2021)
Brewers' spent grain (BSG) is the main by-product derived from the brewing industry, where it accounts for 85% of the total waste generated. The total annual production worldwide of this waste is 39 million tons. This lignocellulosic material is traditionally used as cattle feed and sold at a low retail price (approximately USD 45.00 per ton). However, efforts for the revalorization of this by-product are emerging since research has established that it can be used as a low-cost source of bioactive molecules and commodity chemicals that can bring value to integral biorefinery ventures. Among commodities, phenolic compounds have attracted attention as added-value products due to their antioxidant properties with applications in the food, cosmetic and pharmaceutical industries. These phytochemicals have been associated with antiaging and anticancer activities that have potential applications on cosmetic products. This mini-review summarizes the most relevant extraction techniques used for the recovery of phenolic compounds from BSG while discussing their advantages and shortcomings and the potential applications from BSG bioactive extracts in the cosmetic industry and their reported beneficial effects. This mini-review also makes a brief comment on the role of phenolic compounds extraction in the economic feasibility of an integral BSG biorefinery.